The 6th Polish Zebrafish Society Workshop Abstract Book Kraków14 - 16.02.2024 - Migocka-Patrzałek, Marta (2024)
The 6th Polish Zebrafish Society Workshop Abstract Book. Materiały pokonferencyjne, książka abstraktów zawierająca streszczenia wystąpień ustnych oraz doniesień naukowych zaprezentowanych w formie plakatów naukowych podczas Workshopu, szkolenia, które miało miejsce w Krakowie 14 - 16.02.2024
Keywords: zebrafish; model animals; model organisms; modeling of human diseases; xenografts; high-content screening; Ewing sarcoma; CAR T cells; brain development; neurodevelopmental diseases; brain diseases; immunity; infection; phagocytes; pathogens; toxicity; organogenesis; neurotransmitters; zebrafish behaviour; behavioural assays; anxiolytic drug screening; high throughput; fish viruses; antiviral response; common carp; genome editing; CRISPR/Cas9; disease models; hearing loss; PDX, SCID; L-plastin; bioactive compounds; microbiome; histomorphology; gene expression; model organism; fenoterol; β2-adrenergic receptor; structural analogues; mycotoxins; endocrine disruptive chemicals; cancer; oxidative stress; xenotransplantation; rhabdomyosarcoma; neurodegeneration; Porphyromonas gingivalis; microglia; zebrafish larvae; melanoma; cholesterol; ABCA1; probucol; behavioral pharmacology; cocaine; metal-organic framework; intestinal transit; enterocolitis; citral; anxiety; monoterpenoids; tyrosine kinase inhibitors; endothelium; vascular permeability; cardiovascular toxicity; calcium; protein kinase A (PKA); plasma membrane microdomains; Fluorescence resonance energy transfer (FRET); oxysterols; viral infection; DNA vaccine; McArdle disease; metabolic disorder; skeletal muscle; oncology; xenograft; slc26a4; inner ear malformations; coding and noncoding causative variants